2004
DOI: 10.1007/s00198-004-1678-2
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of osteoporotic patients

Abstract: Osteoporosis has recently been recognized as a major public health problem by some governments and health care providers. Despite significant progress in knowledge about osteoporosis, public awareness is required for effective management if precautions are to be taken. The aim of this study was to evaluate the educational status of osteoporotic individuals, and their awareness about the disease and sources of information. We also aimed to compare the variables between the geographical regions of the country, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 18 publications
5
28
2
9
Order By: Relevance
“…Another study regarding the knowledge of osteoporosis in Turkish patients documented that only 54% of the patients undergoing treatment were aware of their disease (10). Likewise, one of the most striking results of this study is that although 24 patients had a history of fragility fracture, only 17 underwent DXA investigation; 15 patients were under osteoporosis treatment when fracture occurred.…”
Section: Discussionmentioning
confidence: 66%
“…Another study regarding the knowledge of osteoporosis in Turkish patients documented that only 54% of the patients undergoing treatment were aware of their disease (10). Likewise, one of the most striking results of this study is that although 24 patients had a history of fragility fracture, only 17 underwent DXA investigation; 15 patients were under osteoporosis treatment when fracture occurred.…”
Section: Discussionmentioning
confidence: 66%
“…Osteoporosis has recently been recognized as a major public health problem [1,18], it is no longer confined to the growing older population but has implications for all age groups [19]. Hence increasing knowledge of osteoporosis should be a priority for future intervention programs in order to promote specific behavioral strategies for osteoporosis prevention [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in another nationwide study evaluating the educational status of osteoporotic individuals and their awareness about the disease, it was demonstrated that significant differences exist in terms of educational status, clothing style, smoking, level of physical activity, calcium intake, and knowledge about OP between geographical regions of our country. As a result, it was stated that education has profound effects on awareness about OP and many aspects of human behaviour, such as calcium intake, physical activity, clothing style and smoking (11).…”
Section: Discussionmentioning
confidence: 99%